Implementasi Kebijakan Pemerintah Provinsi Daerah Istimewa Yogyakarta tentang Hak Atas Tanah bagi Warga Keturunan - Nurwidyanto, Nurwidyanto; Maksum, Irfan Ridwan (Jurnal Ilmiah Administrasi Publik, 2020)
This research aims to examine the paradigm of thinking of pro and contra parties against the Instruction of The Deputy Governor DIY K.898/I/A/1975. How to implement and what are the factors that influence the implementation of the policy. The approach used in this study is that post positivism approach is qualitative. Implementation of the instruction can be said successful, because from 9 variables of successful policy implementation according to Grindle (Subarsono, 2005), 8 of which have been fulfilled. From the content policy, there are five indicators that have been implemented and three indicators implemented from context of implementation. In the variable content of the policy, the first indicator of interest - the influencing is judged quite well, that are: communication between land stakeholders in Yogyakarta has been going well; existing resources are considered sufficient in the implementation of the policy; the attitude of policy implementers are more required to commit in implementing it and realize its goals and targets; and the last bureaucratic structure in the form of the division of duties has been in accordance with main duties and functions in each of the relevant areas.